Illuminating the Vulnerability of Hegemonic Masculinity through a Performance Analysis of Physically Disabled Men’s Personal Narratives - Scott, Julie-Ann (Disability Studies Quarterly, 2014)
This performance analysis traces the emergence of masculinity in the open-ended narratives of 14 men who self identify as “physically disabled.” The participants range in physical ability, age, relationship status, build, and socioeconomic status. They also range in their responses to the interaction of their ability and gender: mourning, resisting, accepting, and/or embracing their daily performances of physically disabled masculinity. Through bodies defined as the negation of ‘normal,’ they attend to and expose the nuances of the interacting cultural components of hegemonic masculinity that all human beings negotiate, interpret, create and re-create through our interactions. Their stories and insights offer opportunities for us to understand the impossibilities of ideal gender performance all humans co-imagine, reiterate, and pursue but can never realize. Keywords: Performance Analysis, Masculinity, Physical Disability, Personal Narrative